International Protection of the Rights of Children - M. I. Ivanova (Московский журнал международного права, 2011)
The article focuses on issues relating to international protection of the rights of children living in socially dangerous situation. In particular, it examines various international instruments that address the rights of children. Such documents include, for example, the Geneva Declaration of the Rights of the Child (1924), Declaration on the Rights of the Child (1959), the International Covenant on Civil and Political Rights and the International Covenant on Economic, Social and Cultural Rights (1966), Convention on the Rights of the Child (1989) and others. In addition, the article focuses on such leading international organizations like the UN Children’s Fund (UNICEF), as well as specific monitoring mechanism ‒ the UN Committee on the Rights of the Child, which acts as a guarantee of protection of the rights of children living in socially dangerous situation.